2014
DOI: 10.3168/jds.2013-7473
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementing essential fatty acids to pregnant nonlactating Holstein cows and their preweaned calves on calf performance, immune response, and health

Abstract: The objective was to evaluate the effect of supplementing saturated or unsaturated fatty acids (FA) during late gestation of cows and during the preweaning period of calves on growth, health, and immune responses of calves. During the last 8wk of pregnancy, Holstein cattle (n=96) were fed no fat supplement (control), a saturated FA (SFA) supplement enriched in C18:0, or an unsaturated FA supplement enriched in the essential FA linoleic acid. Newborn calves were fed a milk replacer (MR) with either low linoleic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 70 publications
7
53
1
Order By: Relevance
“…Unchanged concentrations of plasma haptoglobin and trend for reduced acid-soluble protein also are indicative that calves fed HLA were not undergoing sickness events (Table 7). Moreover, the trend for increased IFN-γ by stimulated immune cells in vitro (Table 7) may support the hypothesis that calves fed HLA MR had an enhanced ability to mount a proinflammatory response (Garcia et al, 2014b(Garcia et al, , 2015.…”
Section: Hla Mr May Improve Overall Inflammatory Responses and Enhancsupporting
confidence: 61%
See 3 more Smart Citations
“…Unchanged concentrations of plasma haptoglobin and trend for reduced acid-soluble protein also are indicative that calves fed HLA were not undergoing sickness events (Table 7). Moreover, the trend for increased IFN-γ by stimulated immune cells in vitro (Table 7) may support the hypothesis that calves fed HLA MR had an enhanced ability to mount a proinflammatory response (Garcia et al, 2014b(Garcia et al, , 2015.…”
Section: Hla Mr May Improve Overall Inflammatory Responses and Enhancsupporting
confidence: 61%
“…Previously, we reported that linoleic and α-linolenic acids fed to preweaned calves improved their performance and enhanced a proinflammatory response by their immune cells. Moreover, as previously reported (Jenkins and Kramer, 1986), percentages of essential FA in plasma and liver reflected the FA composition of the milk replacer (MR) fed to preweaned calves (Garcia et al, 2014b(Garcia et al, , 2015, as well as affecting the percentage of other longer-chain FA. Therefore, strategic supplementation of FA was expected to modify the FA profile of different tissues and, by either direct or indirect effects, alter cell function.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…In dairy cattle, dams supplemented with prepartum diets enriched in linoleic acid (10) or EPA and DHA (11) produced colostrum with greater concentrations of the respective supplemented FA compared with colostrum from non-supplemented cows. Furthermore, plasma of newborn dairy calves born from dams fed diets enriched in EPA and DHA (12) or linoleic acid (13) had increased concentrations of the FA fed to their dams. In beef cattle, plasma (30 or 60 d of age) and adipose tissue (60 d of age) of calves suckling dams supplemented with high-oleic or highlinoleic safflower seeds had increased concentrations of the supplemented FA in plasma and adipose tissue, compared with calves suckling non-supplemented dams (14) .…”
mentioning
confidence: 99%